(untitled) (Islas, 2025)
Introduction: In Cuba, the process of expansion and modernization of universities in the second half of the 20.th century reached its peak and development with the revolutionary triumph in 1959. The objective of this study is to establish a periodization of Cuban higher education after the revolutionary triumph, referring to its origins and identifying stages based on events of extraordinary significance for the country and the university community. Materials and Methods: The research design is qualitative, documentary, and theoretical with a descriptive approach. The historical-logical analysis method is applied to study the evolution of higher education, utilizing expert criteria, the deductive and inductive methods, and analysis and synthesis of documentary reviews to systematically issue structured judgments and assessments on the topic. Results: This study allowed for the identification of stages and the establishment of a chronology marking the development and transformation of higher education in revolutionary Cuba up to the present state. Conclusions: The development of higher education in Cuba is divided into four stages, highlighting milestones that have shaped its evolution for over 50 years. The system has succeeded in graduating over one and a half million professionals, consolidating fifty Higher Education Institutions (HEIs), forming a faculty of over fifty thousand professors, more than 30% of whom hold Doctor of Science degrees. Additionally, it has fostered active interaction between the university community and society within the Government Management System based on Science and Innovation, the development of public policies and strategic development projects, achieving over 70% of the science and innovation awards from the Academy of Sciences, and maintaining active academic exchange relations with a thousand HEIs from dozens of countries.